Normalizing the Sports Journalism Niche : Coexisting in a Modern News Landscape - Buzzelli, Nicholas R., 1992- (Communication, sport, and society, 2025)
"To offer a comprehensive overview of the current and perceived future state of sports journalism competition, this book draws on insight from 100 qualitative interviews with sportswriters working within five unique subsets of written content (daily newspapers, in-house, team-run media, The Athletic, Substack newsletters, and SB Nation blogging). Using four main communication concepts (gatekeeping, niche gratification, diffusion of innovations, and journalistic boundary work) as the guiding framework, this book examines how various disseminators of written sports information are able to coexist in the modern sports journalism ecosystem by catering to the niche"--